2020
DOI: 10.37185/lns.1.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Impact and Implications of COVID-19: A Narrative Global Status-Quo Review

Abstract: The COVID-19 pandemic is an unprecedented health situation with considerable effects on health systems, economies and societies. Alongside clinically different outcomes for men and women, COVID-19 brought with it social and behavioral changes. There is a need to look at the current pandemic through a gender lens. This review delineates the disproportionate impact of the pandemic with respect to gender and explores the initial literature on gender and COVID-19. Further research can also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The pandemic has also posed challenges for and exacerbated inequities in women's reproductive health [38]. Indeed, women reported a lack of access to sexual and reproductive health services, including contraceptive methods and maternal and child care in emergency situations [37][38][39]. It was found that some vulnerable people, such as displaced populations, non-citizens, migrants, and refugees, that are represented mainly by females and girls do not even have access to PCR testing [40].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pandemic has also posed challenges for and exacerbated inequities in women's reproductive health [38]. Indeed, women reported a lack of access to sexual and reproductive health services, including contraceptive methods and maternal and child care in emergency situations [37][38][39]. It was found that some vulnerable people, such as displaced populations, non-citizens, migrants, and refugees, that are represented mainly by females and girls do not even have access to PCR testing [40].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a lack of representation of females in the decision-making of COVID-19 [39], making them less empowered and widening the gender inequality gap. There has been a dramatic rise in gender-based violence during the pandemic against females around the world.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations